Pedestal or Gutter: Exploring Ambivalent Sexism's Relationship With Abortion Attitudes. (May 2015) - Begun, Stephanie; Walls, N. Eugene
Previous research has examined many aspects of ambivalent sexism theory, although there has been an overall dearth of research conducted on its potential relationship to abortion attitudes. This study aims to compare the extent to which hostile and benevolent sexism, the two primary components of the Ambivalent Sexism Inventory, predict antichoice attitudes. Data were collected at six U.S. colleges and universities ( N = 627), and findings generally support the hypothesis that higher endorsements of either form of sexist beliefs are linked with antichoice attitudes.